COLONIZATION WITH ANTIBIOTIC RESISTANT ORGANISMS IN THE NASAL TRACT AND CLOACA OF DUCKS - Chhabra, D; Majeed , U; Kunal , K; Singh , C (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Ten antibacterial agents belonging to 9 different groups of antibiotics viz. aminoglycosides, cephalosporins, chloramphenicol, fluroquinolones, nitrofurantoin, penicillin, pol mixin tetracyclines and sulphonamides were used for in vitro sensitivity testing. The results indicated that the organisms of nasal passage were 100% resistant to six antibiotic drugs. The organisms showed intermediate sensitivity to four drugs .Similarly, the organisms from cloaca were 100% resistant to Oxytetracycline, Cefuroxime, Ampicillin-cloxacillin, Colistin, Nitrofurantoin and Cotrimoxazole, sensitive to Ciprofloxacin and Ceftriaxone, and intermediate sensitive to Chloramphenicol and Gentamicin. Colonization specifically by antibiotic-resistant organisms followed a similar pattern in both the tracts. The results of nasal swab and cloaca indicate the exact pattern of resistance and very close pattern in sensitivity. Thus, the organisms showed complete resistance towards tetracycline, penicillin, polymixin sulphonamide and nitrofurantoin groups of antibiotics. The results of this study have demonstrated that indiscriminate use of the antibiotics is frequently associated with emergence of resistance in bacteria of ducks.